P-148 Made to measure: improving access to comprehensive specialist palliative care for community based patients. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Marley, Kate; Bayly, Joanne; Aldridge, Claire; Porter, Dawn
Abstract : Background: Woodlands Hospice previously operated a traditional specialist palliative day hospice service, four days weekly, with limited therapy out-patients and domiciliary care. Patient satisfaction was high. However the model of care provided support for a limited number of patients and did not meet needs of all, specifically younger patients, those not wanting to stay all day and those requiring specific and targeted interventions. Aim: To improve access to individually tailored, evidence based specialist palliative care for community based hospice patients. Method: Stakeholder consultation: patients, hospice staff, trustees, volunteers, healthcare professionals Literature review Visits to other hospices Outcome: Reconfigured service improved patient choice and access. Face-to-face contacts increased (2012–2013 = 4032; 2014–2015 = 5059). Building Project (Hospice UK funded): purposely designed rooms enable 1:1 appointments, group therapies and a rehabilitation room for group exercise New Hospice Programme: Twice weekly day therapy- for complex unstable or deteriorating patients with needs that cannot be met in other services Individual out-patient and domiciliary appointments with any member of the multi-professional team Multi-professional group program- enables more patients to access care and peer support: Exercise Breathlessness management Fatigue/anxiety/sleep management Creative arts and legacy work Self-management programme (nurse facilitated, topic based education and peer support) Patient led peer support Bereavement support Introduction of validated outcome measures to evaluate care Conclusion: Access to comprehensive individualised specialist palliative care for community based patients has been improved. Patients move seamlessly between 1:1 appointments, groups and day therapy according to need. Structured evaluation of care continues to influence service improvements.